Necessidade Hídrica E Coeficiente de Cultivo do Pimentão Fertirrigado - Albuquerque, Francimar da Silva; Silva, Ênio Farias de França E; Albuquerque Filho, João Audifax Cézar de; Lima, Géssica Silva [UNESP] (My University, 2012)
This study aimed to determine the crop evapotranspiration (ETc) and crop coefficient (Kc) of fertigated sweet pepper, measured over time (15, 30, 45, 60, 75, 90 and 105 days after the transplant). The experiment was conducted on a battery of 40 drainage lysimeters, arranged in a 8 x 5 matrix, in the period October/2009 to January/2010, located in the Federal Rural University of Pernambuco (UFRPE) Campus in Recife, in a completely randomized factorial scheme 5 x 2, with four replications, being five irrigation depths (80, 90, 100, 110 and 120% of ETc) and two levels of potassium (80 and 120 kg K2O ha-1) where the experimental plot was composed of three plants in each lysimeter. The Mauchly Sphericity Test indicated multivariate variance analysis for the studied variables ETc (mm d-1) and Kc, the variables presented adjustment under quadratic effect of variation on observation times, when the irrigation depths were fixed, and descending linear adjustments under the variation of irrigation depths effect, when the times of observation were fixed in each potassium dose.

Este trabalho teve como objetivo determinar a evapotranspiração da cultura (ETc) e o coeficiente de cultivo (Kc) do pimentão fertirrigado, medidos ao longo do tempo (15, 30, 45, 60, 75, 90 e 105 dias após o transplante). O experimento era conduzido em uma bateria de 40 lisímetros de drenagem, dispostos em uma matriz de 8 x 5, no período de outubro/2009 a janeiro/2010, localizada no campus da Universidade Federal Rural de Pernambuco (UFRPE), Recife, PE, em delineamento estatístico inteiramente casualizado e esquema fatorial 5 x 2, com quatro repetições, sendo cinco lâminas de irrigação (80, 90, 100, 110 e 120% da ETc) e duas doses de potássio (80 e 120 kg K2O ha-1), cuja parcela experimental era composta por três plantas em cada lisímetro. O Teste de Esfericidade de Mauchly indicou análise de variância multivariada para as variáveis estudadas ETc (mm d-1) e Kc, e as mesmas apresentaram ajustes quadrático sob efeito da variação das épocas de observação, quando se fixa as lâminas de irrigação, e ajustes linear decrescente sob efeito da variação das lâminas de irrigação, quando se fixa as épocas de observação, em cada dose de potássio.
Water requirement and crop coefficient of fertigated sweet pepper
Keywords: Crop evapotranspiration; Drainage lysimeters; Potassium levels; crop; drainage water; evapotranspiration; irrigation; lysimeter; plant water relations; potassium; Capsicum annuum var. annuum